Early performance of five newly developed lines of Arabica Coffee under varying environment and spacing in Kenya - Gichimu, Bernard M.; Omondi, C. (My University, 2010)
Knowledge of the effects of environment and genotype by environment (GxE) interaction is important to breeders in making decisions regarding the release of new cultivars. Five Coffea arabica lines coded CR8, CR22, CR23, CR27 and CR30 have been developed by Coffee Research Foundation and are currently being tested for release in various coffee growing zones in Kenya. The objective of this study was to determine the performance of the five advanced breeders lines under varying environment and spacing. Two commercial Arabica cultivars, SL28 and Ruiru 11 were included in the study as check cultivars. The trial was established during the long rain season of March/April 2007 at Kitale in Western Kenya and Meru in Eastern Kenya. The sites were laid out in a Randomized Complete Block Design (RCBD) with ten trees per plot planted at varying spacing of 2M x 1.5M and 2.75M x 2.75M and replicated three times. Growth and yield characters were recorded at the end of first and second year after field establishment. The data was subjected to analysis of variance and effects declared significant at 5% level. Duncans Multiple Range Test (DMRT5%) was used to separate the means. Further analysis were conducted by cluster and principle component analysis. Significant location effect was observed on all parameters but spacing effect was not significant in most of the parameters that were measured.
Keywords: Coffea arabica; Genotype; Environment; Kitale; Meru; growth; yield